A strategic management paper on Kinder Camp Learning Center - Liongson, Jose Luis R. (Animo Repository, 2007)
This is a strategic management paper on Kinder Camp Learning Center. The study attempts to analyze the company from an outsiders point of view with the hope of coming up with sound recommendations for the company's rehabilitation and successful turn-around. Kinder Camp is a preparatory educational institution. It answers the need for early childhood development. It has been in operation since 2001 and is now going on its sixth year of operations. This paper will initially analyze the external environment of which Kinder Camp is a part of. Buy defining the industry, we will look into the threats and opportunities to the industry. The study will also include an analysis of its competitors. Subsequently, the study aims to analyze Kinder Camp internally. The goal is to formulate a strategic plan and specific functional area strategies. Last but not the least, the study aims to create steps on activity implementation with the use of specific frameworks namely the 7-S framework and the 8-SIT framework. No study is complete without financial projections, which is a conclusion to this strategic management paper. It is my hope that this paper would serve as a guiding light to Kinder Camp so that it would head on towards the right direction. The solutions proposed are not absolute, nevertheless they serve as an observers best judgment.